Strategies for Data Lakes in Financial Data Management - Nandish Shivaprasad, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The deployment and optimization of data lakes in financial data management is investigated in this research article. Concerning an ever-growing volume and diversity of data, conventional data management technologies are showing insufficient capability for financial organizations. Providing a scalable and flexible infrastructure for storing and evaluating enormous volumes of organized and unstructured data, data lakes provide a good answer. With an eye on data governance, security, and analytics, this paper investigates many approaches for building, running, and managing data lakes in the financial sector. By means of an extensive literature study and case studies, we pinpoint areas of best practices and difficulties in implementing data lake solutions for financial institutions. The work ends with suggestions for further studies and useful field applications.
Keywords: Data lakes; financial data management; big data; data governance; data analytics